Maternal mortality in Buleleng, Bali, Indonesia (2021–2023): a mixed-methods analysis of clinical, systemic, and sociocultural contributors - Sulyastini, Ni Komang; Linda, Irma Nurma; Armayanti, Luh Yenny; Prabawa, Aditya; Budiawan, Made (MEDISAINS: Jurnal Ilmiah Ilmu-Ilmu Kesehatan, 2025)
Background: Despite increasing access to institutional deliveries in Indonesia, maternal mortality remains a major public health challenge—particularly in decentralized settings where systemic, clinical, and sociocultural barriers persist. Buleleng District in Bali exemplifies this paradox, with maternal deaths continuing to occur in health facilities despite widespread service availability. Objective: This study aimed to analyze the clinical, systemic, and sociocultural contributors to maternal mortality in Buleleng District using a sequential explanatory mixed-methods approach. Methods: The study was conducted in two phases. The quantitative phase involved a retrospective review of 49 maternal death cases reported between 2021 and 2023, sourced from the Buleleng District Health Office. Variables included age, parity, education, timing and place of death, delivery method, and cause of death. Descriptive statistics were applied. The qualitative phase consisted of in-depth interviews with six midwives from five primary health centers. Thematic analysis was used to explore health system barriers, provider capacity, community decision-making, and digital health implementation. Results: Most maternal deaths occurred postpartum (67.3%) and in health facilities (91.8%), with cesarean section as the predominant mode of delivery (83.7%). COVID-19 was the leading cause of death, followed by hemorrhage and hypertensive disorders. Qualitative analysis identified eight key themes, including delays in emergency response, insufficient postnatal monitoring, staff shortages, cultural hesitation in care-seeking, and fragmented digital tools. These findings revealed contributors spanning clinical mismanagement, system-level inefficiencies, and sociocultural decision dynamics. Conclusion: Maternal mortality in Buleleng is shaped by the interplay of clinical complications, systemic gaps, and sociocultural constraints. Addressing these multilevel contributors requires reinforcing postnatal care, expanding digital health integration, strengthening frontline provider capacity, and engaging families and communities in maternal health decisions.